PROTOCOL: A mixed methods systematic review on the effects of arts interventions for at‐risk and offending children and young people on behavioural, psychosocial, cognitive and offending outcomes - Louise Mansfield; Norma Daykin; Neil E. O'Connell; Daniel Bailey; Louise Forde; Robyn Smith; Jake Gifford (Campbell Systematic Reviews, 2023)
Abstract This is the protocol for a Campbell systematic review. The proposed systematic review question is: What is the effectiveness of arts interventions for at‐risk and offending children and young people (8‐25 years)? There are three objectives: (1) To evaluate evidence on the effectiveness and impact of arts interventions on keeping children safe from involvement in violence and crime; (2) To synthesise evidence on factors impacting the implementation of arts interventions, and barriers and facilitators to participation and achievement of intended outcomes; (3) To develop a theory‐of‐change approach to ensure the development of an evidence‐led framework of the processes by which arts interventions might work in preventing offending behaviours.